A new redox-active multisite ligand: synthesis, spectroscopy and electrochemistry of its mono and dinuclear complexes, and the interaction of (E,E)M (M = Ni) complex with Pd-II and Ag-I - ÖZKAYA, ALİ RIZA; KOCA, ATIF (PERGAMON-ELSEVIER SCIENCE LTD, 2004)
A novel redox active (E,E)-dioxime ligand, S,S-bis-[2(2'-ferrocenemethylaminobenzyl)]-dithioglyoxime (LH2), containing ferrocene and flexible aminobenzenesulfanyl-moieties on the periphery has been synthesized from 2-(2'-ferrocenemethylamino)benzenethiol. which was obtained by the reduction of 2,2-pyridylbenzothiazolidine with a large excess of NaBH4. Mononuclear (LH)(2)M (M = Ni-II, Cu-II, Co-II, Fe-II and Mn-II), homodinuclear (LH)(2)(UO2)(2)(OH)(2) and heterotrinuclear (LH)(2)MM'X-2(n) (M = Ni-II and M' = Pd-II, X = Cl-, n = 4 and M' = Ag-1, X = NO3-, n = 2) complexes have been obtained with the metal:ligand ratios of 1:2, 2:2 and 3:2. respectively. Flexible ferrocenemethylaminobenzenesulfanyl moieties bearing two different heteroatoms, -S and -N, on the periphery of the vic-dioxime serve as weak binding sites for Pd-II and Ag-I ions. The detection of H-bonding in all complexes except the uranyl complex by IR revealed square-planar MN4 coordination of the mono- and trinuclear complexes. The MN4 coordination of the Ni-II complex was also determined by the H-1 NMR spectroscopy. The structures of the complexes were characterized by elemental analysis, H-1 NMR, IR, MS, UV-Vis spectral and cyclic voltammetry. The voltammetric analyses of the complexes showed metal, ligand, and ferrocene based signals. The redox chemistry of the complexes exhibited both M-I and M-III oxidation states of the central metals of the complexes. (C) 2004 Published by Elsevier Ltd.
Keywords: vic-dioximes; thiazolidine; ferrocene; transition metal complexes; electrochemistry; TRANSITION-METAL-COMPLEXES; TRINUCLEAR COMPLEXES; LIQUID-CRYSTALS; VIC-DIOXIME; NICKEL(II); COPPER(II); MONONUCLEAR; OXIME; MESOMORPHISM; COBALT(III)